Association between chlorophyll stability and drought tolerance in Robusta coffee - Chutteang, Cattleya; Roonprapant, Prakaimas; Teinseree, Nongluk; Arunyanark, Anuruck (Agriculture and Natural Resources, 2023)
Importance of the work: Chlorophyll stability under water deficit stress might be a promising criterion for drought tolerance selection in Robusta coffee. Objectives: To investigate the effect of water deficit on chlorophyll stability and photosynthesis in Robusta coffee, as well as to assess the drought tolerance of Robusta coffee genotypes and the relationship between chlorophyll stability and drought tolerance in Robusta coffee. Materials & Methods: In hydroponics experiments, six Robusta genotypes were evaluated to compare control and water deficit conditions. Total dry matter, chlorophyll density (chlorophyll content per unit leaf area), chlorophyll content (chlorophyll content per plant) and the soil plant analysis development (SPAD) index were all measured. In addition, the net photosynthetic rate (Pn), transpiration rate (E) and maximum quantum efficiency (Fv/Fm) were determined. Results: Water deficit stress significantly reduced all chlorophyll parameters, photosynthesis and total dry weight parameters. The total dry weight and chlorophyll parameters differed significantly between genotypes. Significant relationships between chlorophyll parameters and Pn, E and Fv/Fm were found in water stress conditions (Pearson’s correlation coefficient, r = 0.49* to 0.68**, where * = significant at p < 0.05 and ** = significant at p < 0.01). The total dry weight of Robusta coffee was related to the chlorophyll content, chlorophyll density and the SPAD index (r = 0.51* to 0.90**). Furthermore, the chlorophyll density had a strong positive relationship with the SPAD index (r = 0.85**). Main finding: Chlorophyll stability was an important mechanism of drought tolerance in Robusta coffee. The SPAD chlorophyll meter could be used to rapidly assess relative chlorophyll status in coffee genotypes and to select drought tolerance in Robusta coffee.